Indoor air quality perception: Enablers and inhibitors of perceived occupant comfort - Inês Veiga; Tiago Oliveira; Mijail Naranjo-Zolotov; Ricardo Martins; Stylianos Karatzas (Environment International)
Growing environmental and public health concerns have increased the need for healthy buildings, with indoor air quality (IAQ) emerging as a priority. While technological advancements in IAQ management have progressed, research often overlooks individual comfort perception and behavioral factors influencing it and disconnects IAQ improvements from behavioral insights. This study explores how personal characteristics, perceived inhibitors, and enablers shape comfort perception in indoor environments managed by Internet of Things-based IAQ management technologies (IAQMTs). Given the EU’s growing emphasis on smart, energy-efficient, and occupant-centered buildings, we examine comfort perceptions across seven European countries to inform user-centered IAQ strategies aligned with policy goals. Grounded in the dual-factor theory, we employed a survey-based approach in the European context and analyzed responses from 2800 individuals using partial least squares structural equation modeling (PLS-SEM). Our model demonstrated strong explanatory power, accounting for over 65 % of the variance in perceived IAQ and comfort in public environments. Key enablers are intuitiveness, response efficacy, and hedonic motivation, while convenience is not. Information and privacy concerns are not inhibitors. Health consciousness and environmental consciousness are important individual characteristics when it comes to perception. Perceived good IAQ was the strongest predictor of comfort in public spaces. The findings emphasize the importance of intuitive, transparent, and engaging IAQMTs that visibly demonstrate pollutant reduction and comfort enhancement. We recommend that building managers and technology developers incorporate user-centered features, such as clear interfaces, gamification elements, personalized controls, and communication strategies highlighting health and environmental benefits, to foster adoption and improve occupant comfort. Our findings support a human-centered approach, integrating behavioral insights into environmental health science, focusing beyond technical metrics and more on occupant beliefs and perceptions, supporting strategies that align with user needs and EU goals.